HOSPITALITY REGISTERS USED BY FRONTLINERS OF ATRIA RESIDENCE GADING SERPONG TANGERANG - Ratmo Ratmo; Tutut Sumartini; Ida Cahyani (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2024)
In hospitality industry, there are many kinds of English terms used by the staff both written and spoken. These English terms in hospitality industry are part of English for Specific Purposes (ESP) which are called registers. This research aims to find out registers as the formal English terms used by the front liners or Front Office Staff of Atria Residence Gading Serpong Tangerang, and to analyse the lexical and contextual meanings of the registers used. This research employs descriptive qualitative method to collect and analyse the data. The subject of this study is the staff of Front Office department of Atria Residence Gading Serpong. The data will be obtained through participant observation, semi- structured interview and review of the documents. In collecting data, some conversations between guests and front office staff are recorded. The findings uncover the majority of terms used in Front Office department in the hotel, and to which categories they are used in general and in specific context. This research also reveal the terms have different meanings in both lexical and contextual aspects. As one of language varieties in sociolinguistics, hospitality registers are discipline language or formal language the hotel staff must use in their work place as to follow standard of operational procedure (SOP). Moreover, the English terms used in a specific work setting are part of English for Occupational Purpose (EOP) as a part of English for Specific Purpose (ESP).